A fiber-optic spectroscopic setup for isomerization quantum yield determination - Volker, Anouk; Steen, Jorn D.; Crespi, Stefano (Beilstein Journal of Organic Chemistry, 2024)
A spectroscopic setup for isomerization quantum yield determination is reported. The setup combines fiber-coupled LEDs, a commercially calibrated thermopile detector for measurement of the photon flux, and a fiber-coupled UV–vis spectrometer. By solving the rate equations numerically, isomerization quantum yields can be obtained from the UV–vis absorption spectra. We show that our results for the prototypical photoswitch azobenzene are in excellent agreement with the literature. The analysis of the errors showed that the quantum yields determined using this method are in the same order of magnitude as when using actinometry, thus demonstrating the reliability of our setup.
Keywords: isomerization; molecular photoswitches; photochemistry; photon flux; UV–vis spectroscopy